Global Stabilization of High-Order Time-Delay Nonlinear Systems under a Weaker Condition - Nengwei Zhang; Enbin Zhang; Fangzheng Gao (Abstract and Applied Analysis)
Under the weaker condition on the system growth, this paper further investigates the problem of global stabilization by state feedback for a class of high-order nonlinear systems with time-varying delays. By skillfully using the homogeneous domination approach, a continuous state feedback controller is successfully designed, which preserves the equilibrium at the origin and guarantees the global asymptotic stability of the resulting closed-loop system. A simulation example is given to demonstrate the effectiveness of the proposed design procedure.